Investigation of Strength Parameters of PVA Fiber-Reinforced Fly Ash-Soil Mixtures in Large-Scale Direct Shear Apparatus - Gohari Lasaki, Ashkan; Jamshidi Chenari, Reza; Shamsi Sosahab, Javad; Jafarian, Yaser (Salehan Institute of Higher Education, 2018)
Soil reinforcement is an old and still efficient technique in improving soil strength and stiffness properties. Current paper aims at quantifying the effects of different inclusions on mechanical behavior of fiber-reinforced cemented soil. An experimental program was conducted to study simultaneous effects of randomly oriented fiber inclusions and cement stabilization on the geotechnical characteristics of fly ash-soil mixtures. Chamkhaleh sand, polyvinyl alcohol (PVA) fiber, cement and fly ash with some water were mixed and compacted into large scale direct shear apparatus with three equal layers. PVA fibers were randomly distributed in three compacted layers at predetermined weight contents. Direct shear tests were carried out on fly ash-soil specimens prepared with different cement, fly ash and polyvinyl alcohol contents, and 7 different curing periods. Results show that cement increases the strength of the raw fly ash-soil specimens. The fiber inclusion further increases the strength of the cemented and uncemented soil specimens and transforms their brittle behavior to ductile behavior. The fiber reinforcement and distribution throughout the entire specimen results in a significant increase in the strength of fly ash -soil- cement mixtures.